Factors affecting lymphocyte collection efficiency for the manufacture of chimeric antigen receptor T cells in adults with B‐cell malignancies. Issue 5 (6th February 2019) - Tuazon, Sherilyn A.; Li, Ang; Gooley, Theodore; Eunson, Thomas W.; Maloney, David G.; Turtle, Cameron J.; Linenberger, Michael L.; Connelly‐Smith, Laura S.
Abstract : BACKGROUND: The clinical and procedural parameters that affect the optimal collection of lymphocytes for the production of chimeric antigen receptor (CAR) T cells remain undefined but are increasingly important, as commercial products are now available. We evaluated determinants of low lymphocyte collection efficiency (CE) and the rate of successful CAR T‐cell manufacture in middle‐aged and older adults with advanced B‐cell malignancies. STUDY DESIGNS AND METHODS: Mononuclear cell collections using two apheresis platforms (COBE Spectra and Spectra Optia, Terumo BCT) from patients participating in a CD19‐directed CAR T‐cell therapy trial were reviewed. Patient‐ and disease‐specific factors, peripheral blood counts, apheresis parameters, and product cell counts were analyzed to determine effects on lymphocyte CE. RESULTS: Ninety‐two apheresis events from patients with acute lymphocytic leukemia (ALL) (n = 28), chronic lymphocytic leukemia (n = 18), and non‐Hodgkin lymphoma (n = 46) were available for analysis. Forty‐one collections (45%) had a lymphocyte CE of <40%. On multivariable analysis, age (every 10‐year increase, odds ratio [OR] = 1.51; p = 0.034), disease type (chronic lymphocytic leukemia vs. ALL, OR = 0.24; p = 0.052; non‐Hodgkin lymphoma vs. ALL, OR = 0.20; p = 0.009) and precollection platelets (every 10 × 10 3 /μL increase, OR = 1.07; p = 0.005) were appreciably associated with a lymphocyte CE of <40%. No major apheresis complications occurred. CONCLUSIONS: Lymphocyte collection at our center was well tolerated and 100% successful in manufacturing CD19‐directed CAR T cells from adult patients with B‐cell malignancies despite low CE in some patients. A diagnosis of ALL, advancing age, and higher preapheresis platelet counts were observed to be associated with low CE.